Key issues and challenges of green consumer in consuming green product an insight from the emerging country: Malaysia - Ogiemwonyi, Osarodion; Harun, Amran; Othman, Bestoon Abdulmaged; Ismael, Darbaz Anwer; Ali, Raman (Hampstead Psychological Associates, 2019)
Climate change is a serious consequential threat which has been a serious concern among scholars and business clients. As such green behaviour on performing what, how, when, where and why to satisfy consumer need to encounter a function that plays an influential factor on the planet. Therefore, environmentally friendly consumption is an option to solves these issue bothering on environmental damage. This research study follows a systematic literature review based on the conceptual context. Therefore, we systematically explore key issues that trigger environmental problems specifically in Malaysia. The emergence of environmental-related issues or problems and increased awareness towards green consuming have received more attentions especially among consumers and enterprises who have demonstrated positive impact towards nature in the emerged nations, but the trends remain unobserved in a creating and emerging nation such as in the Malaysia context. Therefore, our study contributes to the growing literature on the sustainable planet by identifying major key issues and challenges that affect environmental friendly products and the natural environment. Besides, the implication and recommendations for further research are also discussed. Hence, this paper will provide valuable insights into the emerging society, especially in Malaysia with a view to restoring the planet for the benefit of all.